The Assessment of Daily Energy Expenditure of Commercial Saturation Divers Using Doubly Labelled Water - Deb, Sanjoy K.; Dolan, Eimear; Hambly, Catherine; Speakman, John R.; Eftedal, Olav; Zariwala, Mohammed Gulrez; Eftedal, Ingrid (Frontiers in Physiology, 2021)
Commercial saturation divers are exposed to unique environmental conditions and are required to conduct work activity underwater. Consequently, divers’ physiological status is shown to be perturbed and therefore, appropriate strategies and guidance are required to manage the stress and adaptive response. This study aimed to evaluate the daily energy expenditure (DEE) of commercial saturation divers during a 21-day diving operation in the North Sea. Ten saturation divers were recruited during a diving operation with a living depth of 72 metres seawater (msw) and a maximum working dive depth of 81 msw. Doubly labelled water (DLW) was used to calculate DEE during a 10-day measurement period. Energy intake was also recorded during this period by maintaining a dietary log. The mean DEE calculated was 3030.9 ± 513.0 kcal/day, which was significantly greater than the mean energy intake (1875.3 ± 487.4 kcal; p = 0.005). There was also a strong positive correction correlation between DEE and total time spent performing underwater work (r = 0.7, p = 0.026). The results suggested saturation divers were in a negative energy balance during the measurement period with an intraindividual variability in the energy cost present that may be influenced by time spent underwater.